WUJUD ISLAM RAHMATAN LIL ÂLAMIN DALAM KEHIDUPAN BERBANGSA DI INDONESIA - Muhammad Nur Jamaluddin (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2020)
The realization of Islam Rahmatan Lil'alamin both in the world in general and in Indonesia in particular is facing problems such as violence, extremism, radicalism, and terrorism on behalf of Islamic religion. This research is a literature study that discusses the concept of Islam Rahmatan Lil'alamin with a comprehensive and holistic is important in the midst of the strengthening of discourse and action between the Islamic movements in Indonesian nationality. Rahmatan Lil'alamin as an embodiment of Islamic ideals in nationality can be acctualized by 3 (three) ways, namely: (1) have extensive knowledge and understand the development of technology and science; (2) Not the emotion in Bergama; and (3) be careful in every speech, deed, and action.